Contact and non-contact methods for optical spectroscopy and imaging in epithelial cancer diagnosis and tissue viability assessment - Zhu, Caigang (2014)
This dissertation presents a series of studies in the development of contact and non-contact optical measurement techniques, and Monte Carlo (MC) based data analysis methods in visible diffuse reflectance and auto-fluorescence spectroscopy/imaging for tissue characterization. Their applications in early epithelial cancer diagnosis and tissue viability prediction are demonstrated. Firstly, the background in epithelial cancer and flap tissue viability as well as the principles/state of art of optical spectroscopy and imaging in tissue optics was presented in Chapter 1. Then a general survey on the capability of MC modeling of light transport in tissues was provided in Chapter 2 due to the importance of MC modeling in the field of tissue optics. The recent progress in the development of methods for speeding up MC simulations and the potential directions of future development were discussed. Based on the literature review on MC methods given in the previous Chapter, we developed a MC method to simulate diffuse reflectance and fluorescence from a layered tissue with embedded objects to mimic an early epithelial caner model in Chapter 3. With the help of this MC method, a series of numerical studies were performed to provide the guidelines for the selection of a proper epithelial cancer model in MC simulations. However, it is very time consuming to use the standard MC method for the simulation of light transport in a layered tissue with embedded object. To overcome this problem, a hybrid method, in which the scaling method and the perturbation MC method were integrated coherently, was proposed and validated to accelerate the simulations of diffuse reflectance from a layered tissue with embedded objects in Chapter 4. This method is suitable for simulating diffuse reflectance spectra or creating a MC database to extract optical properties of an early epithelial cancer model. All the above studies were designed for contact optical measurements using fiber-optics. However, inconsistent probe-sample contact could induce significant errors in diagnosis of early epithelial cancer. To address this problem, lens based setup was investigated for non-contact optical measurements in Chapter 5 and Chapter 6. We firstly developed a MC method to simulate diffuse reflectance and fluorescence measurements by convex lenses based non-contact setup. Then a series of numerical studies were performed to achieve depth sensitive diffuse reflectance and fluorescence measurements on the early epithelial cancer model. After that experimental studies were performed by a lens based optical system to validate the MC results and confirm the findings obtained in simulation study. We further extended the lens based non-contact spectroscopy system to an imaging setup with a larger field of view to perform depth sensitive color imaging on an early epithelial cancer phantom in Chapter 7. In the proposed setup, a micro-lens array was used to induce multi-focal illumination and a tunable lens was utilized to map multiple light foci into the tissue phantom at a range of depths. Another imaging lens was used to image light into a 3-CCD camera. The study performed on the epithelial cancer phantoms demonstrated that our method could be potentially used as a clinical tool for the diagnosis of early epithelial cancer. In addition to the numerical and phantom studies in epithelial cancer diagnosis, an animal study was also performed in Chapter 8 to predict tissue viability in flap surgery using a dual-modal system capable of performing both visible diffuse reflectance and auto-fluorescence spectroscopy. The results showed that either visible diffuse reflectance spectroscopy or auto-fluorescence spectroscopy alone can predict the skin viability accurately; however, auto-fluorescence spectroscopy was more sensitive to tissue changes in the first two hours after the induction of ischemia. It was feasible to predict flap failures in the first two hours when using auto-fluorescence spectroscopy alone. Moreover, it is possible to predict flap failures even in the first 15 minutes with high accuracy when using diffuse reflectance and auto-fluorescence spectroscopy simultaneously. In Chapter 9, we summarized that UV-visible diffuse reflectance and auto-fluorescence spectroscopy or imaging are promising tools for early epithelial cancer diagnosis and tissue viability prediction. Further refinement of these techniques would help advance the use of optical spectroscopy and imaging in clinical settings for tissue characterization in an even larger range of clinical applications.